Different Backgrounds and English Learning Styles of Bangkok University Student - Munsakorn, Nuttanuch (Mediterranean Journal of Social Sciences, 2012)
The purpose of this research was to investigate the influence demographics, gender, faculty, and level of generalEnglish has on students’ learning styles. Subjects were 410 students representing Accounting, Business Administration, andEconomics faculties and studying Business English courses at Bangkok University. A Perceptual Learning Style PreferenceQuestionnaire: PLSPQ (Reid, 1987) was used for collecting data via a five point Likert scale. Data were analyzed and calculatedin percentage, mean, standard deviation and Chi-squared test at the level of 0.05.The results show that Bangkok Universitystudents do not have a specific style of learning English. The three main forms of learning English are; study in a group, learningand practicing in different situations, and listening respectively. Some results varied based on gender, faculty and levels ofacademic performance in general English variables. However, the styles of learning English did not.